The mapping of Indonesian collocations: A contrastive analysis with English collocations - Dewiyanti, Sri; Yuliyawati, Sri Nur; Saudin, Saudin; Meilinda, Lina (Indonesian Journal of Applied Linguistics, 2024)
Recent years have witnessed a growing interest in research on English collocations, yet studies focusing on Indonesian collocations remain underexplored. Collocations are crucial for language acquisition as proficiency in collocations is indicative of language competence. This study, therefore, intends to reveal and map the patterns of Indonesian lexical and grammatical collocations through a contrastive analysis with English collocation patterns. The research was primarily qualitative,utilizing the phraseological approach supported by a corpus for collocation identification. The word classes of the collocation patterns were determined using KBBI V (the unabridged Indonesian dictionary). Data were sourced from main reports of Tempo magazine and headlines of Kompas as well as Pikiran Rakyat newspaper, comprising a total of 14,206 words. The data yielded a total of 1,488 instances of Indonesian collocations, divided into lexical collocation with 994 instances (66.8%) and grammatical collocation with 494 instances (33.2%). The investigation reveals nine sub-types of Indonesian lexical collocations, seven of which correspond to English lexical collocation sub-types while the other two are Indonesian-specific patterns. With respect to grammatical collocation, Indonesian possesses 14 sub-types, with eight aligning with English patterns and six unique to Indonesian. Future studies are required to delve more into and shed light on Indonesian collocations.